Improving Student Learning Outcomes of Class VII.A SMP Negeri 2 Kendari in Indonesian Language Subjects Through Cooperative Learning Model Type of Student Team Achievement Division - Saemina (Persatuan Guru Republik Indonesia Provinsi sulawesi Tenggara, 2022)
The purpose of this study was to improve the learning outcomes of class VII. A student of SMP Negeri 2 Kendari in Indonesian subjects through a cooperative learning model of the student team achievement division type. Cooperative learning consists of various types, including the STAD, Jigsaw, Investigation Group, and NHT. Classroom action research through the application of the Student Teams Achievement Division (STAD) cooperative learning model out with the following activities: (1) delivering learning objectives; (2) presenting information about learning materials; (3) organizing students in study groups; (4) question and answer in study groups; (5) guiding study groups that are working together; (6) giving awards; and (7) conduct individual evaluations. The implementation of this classroom action research uses the following procedures: (a) planning; (b) implementation; (c) observation; (d) reflection. Student learning outcomes in the implementation of the first cycle of 34 students who took the test obtained data as many as 23 students (67.65%) stated that the student's scores were in the complete learning category, and in the implementation of the second cycle of 34 students who took the test data obtained as many as 30 students (88, 24%) stated that the student's score was in the complete learning category. Thus, the application of the Student Teams Achievement Division type of cooperative learning model can improve the learning outcomes of class VII.A students of SMP Negeri 2 Kendari.